Effect of perioperative immunonutrition intervention among gynecological cancer patients: a systematic review - Ho, ChiouYi; Mohd Yusof, Barakatun Nisak; Abdul Majid, Hazreen; Mat Daud, Zulfitri Azuan (Elsevier, 2024)
Background: Gynecologic cancer (GC) patients often experience systemic inflammation, malnutrition, and compromised postoperative outcomes. This systematic review aims to comprehensively synthesize existing data regarding the impact of perioperative immunonutrition (IMN) intervention on GC patients. Methods: The databases of CENTRAL, EMBASE, Web of Science, and the Cochrane Library were used to conduct a literature search, supplemented by internet search engines and manual searches. Publications released between January 2009 and October 2023 was identified, reviewed, and data extracted. Results: The review encompasses six studies involving 712 patients, comprising two randomized controlled trials (RCTs), two prospective studies, and two retrospective cohort studies. Three studies prescribed IMN perioperatively; two pre-operatively and one post-operatively. Four out of six studies reported less post-operative infection and complications. Two studies reported shorter hospitalization using the IMN formula. One study reported a longer hospitalization with IMN supplementation. Overall survival showed no significant difference in the two studies. Four studies reported positive modulation of inflammatory markers and lymphocytes as outcomes, with IMN formulas. Discussion and conclusion: Perioperative IMN emerge as a promising intervention, demonstrating notable benefits included shortened hospitalization as well and positive modulation of inflammatory markers.